8(3x-7)=-6(x+7)

Simple and best practice solution for 8(3x-7)=-6(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(3x-7)=-6(x+7) equation:



8(3x-7)=-6(x+7)
We move all terms to the left:
8(3x-7)-(-6(x+7))=0
We multiply parentheses
24x-(-6(x+7))-56=0
We calculate terms in parentheses: -(-6(x+7)), so:
-6(x+7)
We multiply parentheses
-6x-42
Back to the equation:
-(-6x-42)
We get rid of parentheses
24x+6x+42-56=0
We add all the numbers together, and all the variables
30x-14=0
We move all terms containing x to the left, all other terms to the right
30x=14
x=14/30
x=7/15

See similar equations:

| -2x^2+52x+240=0 | | 5m−m=8 | | -2-8r=-8-2r | | x-7+3=5 | | -3(23x+6)=-26 | | 3(2+8b)-5(-6b+7)=79 | | 6x-2+2x=-2+4x+8 | | 30+15x=165 | | 2/7y-5/61=1/6-5/7y= | | z5− -14= 18 | | 15(x-13)=495 | | −3(23x+6)=−26 | | 5x+2=127x= | | 15(x-13)=12 | | 2x-3=x+62 | | k-2/2=2 | | 53-2/3j=59 | | 2/7y-5/6=11/6-5/7y | | v+1/3=2 | | 2/7y-5/6=11/6-5/7y= | | h/3-15=-7 | | 9n−11=52 | | 2220=-5x | | 7-5g=-38 | | Y=3x-3x | | 3x+3=8x-2 | | 15+9s=42 | | y+5/2=3 | | 7m+4=81 | | 8-0.02=2.23x+3.5 | | 3f-15=-7 | | -4x+9=-4x-9 |

Equations solver categories